2019
DOI: 10.1016/j.jvir.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Nylon Fibered Versus Non-Fibered Embolization Coils: Comparison in a Swine Model

Abstract: Purpose: To determine whether nylon fibers improve the performance of platinum embolization coils in porcine arteries. Materials and Methods: Platinum 0.035" embolization coils, both with and without nylon fibers, were used to embolize a total of 24 hindlimb arteries in 6 swine: 12 with fibered coils and 12 with non-fibered coils. Apart from fibers, the coils were identical. Immediate and late results were studied, including number of coils needed to achieve vessel occlusion and durability of occlusion at 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The metal spire serves as a support structure for the fibered material with no or insignificant effect on blood clotting. 28–31 Scanning Electron Microscopy image analyses (Figure 1) showed that the FDC used in this study bear multi-filament fibers in 30 localized clusters (plumes) of 24 to 27 individual filaments, with each individual filament presenting a length of 2375 ± 154 µm.…”
Section: Methodsmentioning
confidence: 87%
“…The metal spire serves as a support structure for the fibered material with no or insignificant effect on blood clotting. 28–31 Scanning Electron Microscopy image analyses (Figure 1) showed that the FDC used in this study bear multi-filament fibers in 30 localized clusters (plumes) of 24 to 27 individual filaments, with each individual filament presenting a length of 2375 ± 154 µm.…”
Section: Methodsmentioning
confidence: 87%
“…The use of nylon-based suture for this preliminary study was adopted because it is used in the manufacture of several prostheses deployed in vascular surgery, and is nowadays incorporated into coils to enhance its thrombogenicity [20,21]. It can therefore be considered safe considering its bio-toxicity and its degradation in contact with the blood elements.…”
Section: Discussionmentioning
confidence: 99%
“…The second aim is to prevent non‐target embolization and an excess of vessel loss. In theory, advanced technical qualities of coils such as enhanced thrombogenesis (fibered coils), controlled detachment (detachable coils) and coating (expanding hydrogel coating) 97 should enable better results (reduced incidence of reperfusion) and reduced complication rates, which were proven in animal models 98,99 . Only one randomized trial comparing outcomes with detachable versus pushable coils is available; no significant differences were reported at 1‐year follow‐up 100 …”
Section: Pavm Embolizationmentioning
confidence: 99%
“…In theory, advanced technical qualities of coils such as enhanced thrombogenesis (fibered coils), controlled detachment (detachable coils) and coating (expanding hydrogel coating) 97 should enable better results (reduced incidence of reperfusion) and reduced complication rates, which were proven in animal models. 98,99 Only one randomized trial comparing outcomes with detachable versus pushable coils is available; no significant differences were reported at 1-year follow-up. 100 Otherwise, no randomized clinical trials are available for the comparison of the efficacy between various types of coils (fibred vs. non-fibred vs. hydrogel), the comparison of coils versus plugs/occluders or various types of plugs/occluders or plugs/occluders without additional coil placement versus plugs/occluders with additional coil placement.…”
Section: Coils or Plugsmentioning
confidence: 99%